Konsep Matching dalam Budaya Sida Perkawinan Masyarakat Manggarai - Susana Purnamasari Baso; Maria Odriana Veronika Moi; Leopold Melkiano Triangga Dawu (Departement of Mathematics Education, 2023)
This study aims to examine the applicability of the concept of matching or matching concept as well as examine the meaning of costs in the tradition of